Studies about professional development: from the choice up to the rupture of the teaching career - Folle, Alexandra; Nascimento, Juarez Vieira do (Journal of Physical Education (Maringá), 2008)
The aim of this study was to accomplish a systematic review of the researches which approach teaching professional development, especially in Physical Education. Two sources of information were utilized: searches based on electronic data (LILACS, SCIELO, SCOPUS, SPORT DISCUS, WEB of SCIENCE, ERIC) from describers and searches in referential lists from the studies which were found, which resulted in the inclusion of other types of scientific production. Only studies accomplished between 1990 and 2007 were considered. From 65 investigations that met the inclusion criteria, 40 were national studies and 25 were international ones. Results indicate that the majority of studies were performed with teachers who teach in elementary school, the most frequent collecting data instrument is the interview, and the methodological approach which predominated was teaching life stories. Studies revealed that teaching profession choice is as much influenced by intrinsic and altruistic reasons as by extrinsic, in addition, career entering varies between discovery and surviving feelings. Diversity of professional trajectories confirms that the evolution in teaching career is not linear, occurring some advances and retreats. It is also shown that teaching dispel can be either serene or bitter, depending on the teacher’s intervention context.